Pharmacokinetics of cefpirome following intravenous and intramuscular administrations in healthy and febrile sheep (Ovis aries) - SARVAIYA, VAIDEHI N; SADARIYA, KAMLESH A; BHAVSAR, SHAILESH K; THAKER, ASWIN M; MODI, RAKESH J (The Indian Journal of Animal Sciences, 2023)
Cefpirome is fourth generation cephalosporin class of drug, which facilitates rapid penetration through the outer membrane of Gram-negative bacteria and results in potent activity against Gram-negative pathogens. As fever is one of the most common manifestations in bacterial diseases, the study was undertaken to investigate pharmacokinetics of single dose intravenous and intramuscular administrations of cefpirome (10 mg/kg of body weight) in healthy and lipopolysaccharide (LPS) induced febrile sheep as well as to perform PK-PD analysis using MIC values reported in previous studies and the pharmacokinetic parameters obtained in this study. Following intravenous and intramuscular administrations of cefpirome in healthy sheep, the plasma drug concentration was detected up to 12 h, while plasma drug concentration was detected up to 18 h following intravenous and intramuscular administrations in febrile sheep. Induction of febrile state significantly altered pharmacokinetic profile of cefpirome including significant increase in the mean values of t½β, AUC0-∞ and MRT while significant decrease in the mean values of Vdarea, Vdss following intravenous administration, while significant decrease in the mean values of Vdarea and ClB, whereas significant increase in the mean values of t½β, Cmax, AUC0-∞ and MRT following intramuscular administration of cefpirome as compared to their respective mean values in healthy sheep. Based on pharmacokinetic-pharmacodynamic integration, an optimal intramuscular dosage regimen of 10 mg/kg once daily for cefpirome in febrile sheep was predicted for targeted average MIC of ≤ 0.25 μg/mL.